Assessment of the Balance of Aspects of the Socio-Ecological and Economic Efficiency of the Organization Activity Based on the Dynamic Standard Method - K. S. Hruznevich (Статистика и экономика)
In modern conditions, the main goal of the organization activity is not only to obtain a commercial effect in the form of profit, but also its stable development, which depends on the health of people and the quality of the environment. Understanding this forms a new look at the organization only a moderate consumption of resources, the preservation of the natural environment for the sake of future generations can allow it to become effective in the long term. This requires a transition from the traditional economic understanding of efficiency to the socio-ecological and economic one, which is based on the balance of its aspects.The aim of the study is to develop the author’s definitions of the categories “socio-ecological and economic efficiency”, “balance”; as well as an assessment of the balance of aspects of efficiency based on the dynamic standard method. The objectives of the study include: a) to develop the author’s definitions of the categories of socio-ecological and economic efficiency and balance; b) consider approaches to assessing the balance at the micro and meso levels; c) form a system of indicators for assessing the effectiveness of the organization; d) develop a normative series of growth rates of performance indicators and compare with the actual one using the example of a particular organization.Materials and methods. In preparing the article, methodological approaches to assessing the balance at the micro and meso levels were studied, namely: the essence, content, statistical tools underlying them, their shortcomings and the ability to assess the balance of aspects of the effectiveness of the organization activity were identified. The assessment was carried out using the dynamic standard method, for which the normative order of subordination of the indicators included in it was determined. For the assessment, we used data from the industrial organization, the main activity of which is the production of outerwear (Republic of Belarus, Vitebsk region).Results. As a result of writing the paper, the author’s definitions of the studied categories were developed, a system of indicators for certain aspects of the effectiveness of the organization activity was formed, priorities in growth rates were determined and the normative ranks of the selected indicators were established. Based on the data of a specific organization, a comparison was made between the normative and actual modes of functioning based on the calculation of the Spearman’s rank correlation coefficient and Kendall’s rank correlation coefficient. The conclusion is made, theoretical directions of increasing the consistency of tempo characteristics are proposed.Conclusion. The article points out the degree of balance of certain aspects of efficiency (social, environmental and economic) on the example of a real business entity, which made it possible to form theoretical directions for eliminating their imbalance.